2017
DOI: 10.1016/j.jacr.2017.08.051
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria ® Multiple Gestations

Abstract: Women with twin or higher-order pregnancies will typically have more ultrasound examinations than women with a singleton pregnancy. Most women will have at minimum a first trimester scan, a nuchal translucency evaluation scan, fetal anatomy scan at 18 to 22 weeks, and one or more scans in the third trimester to evaluate growth. Multiple gestations are at higher risk for preterm delivery, congenital anomalies, fetal growth restriction, placenta previa, vasa previa, and velamentous cord insertion. Chorionicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 99 publications
0
37
0
Order By: Relevance
“…This is well-established since it is known that the differentiation of a yolk sac and an amnion occur very close to each other in time, around 6-8 days after fertilization [5]. If a single yolk sac is detected, a repeat first trimester scan is undertaken, or a refer to a tertiary center with advanced experience in multiple pregnancies can be helpful [3,4].…”
Section: Number Of Yolk Sacsmentioning
confidence: 99%
See 4 more Smart Citations
“…This is well-established since it is known that the differentiation of a yolk sac and an amnion occur very close to each other in time, around 6-8 days after fertilization [5]. If a single yolk sac is detected, a repeat first trimester scan is undertaken, or a refer to a tertiary center with advanced experience in multiple pregnancies can be helpful [3,4].…”
Section: Number Of Yolk Sacsmentioning
confidence: 99%
“…Salomon et al [13] suggested that the CRL of the smallest fetus can estimate more accurately the gestational age, if the intertwin CRL discrepancy is less than the 95th percentile, using charts from studies. An interesting finding is that if the intertwin discordance in CRL is higher than 10%, the possibility of pregnancy loss, aneuploidy, or congenital anomalies is increased [3,14,15].…”
Section: Time Of Embryo Splitting (In Days)mentioning
confidence: 99%
See 3 more Smart Citations